2009
DOI: 10.1179/174329008x286721
|View full text |Cite
|
Sign up to set email alerts
|

Supersolidus liquid phase sintering of Al6061/SiC metal matrix composites

Abstract: The aim of the present work is to study the effect of reinforcement content and sintering temperature on the densification and microstructural development during sintering of Al6061/SiC composite compacts. Prealloyed Al6061 powder was mixed with various amounts of SiC particles up to 27 vol.-% and compacted at 350 MPa. Sintering was carried out in a dry nitrogen atmosphere at 580-620uC. It was shown that the presence of SiC particles retards the densification of the prealloyed powder during solid phase sinteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…For the last few decades, the aluminum alloys have been widely used in many industrial fields such as aerospace, architectural con struction, and automotive, because of the nature of lightweight, high corrosion resistance, high thermal conductivity, etc [13][14][15], In order to meet the demand of the more comprehensive mechani cal properties (e.g., the enhanced tensile strength and wear/ tribological performance), the development of the particle rein forced aluminum matrix composites (AMCs), especially the SiC particle reinforced AMCs, attracts the considerable attention, exhibiting the inspiring prospects for development [30], The SiC particle reinforced AMCs have the significant potential for the applications in the aircraft and automotive industries, because of the characteristics of lightweight, high strength, high elastic mod ulus, good wear resistance, and low coefficient of thermal expan sion [31][32][33], Currently, the parts manufactured from the SiC particle reinforced AMCs have been successfully applied in both military and civilian fields, such as aircraft ventral fin [34], wing panels [31], pistons and engine blocks [35], Powder metallurgy (PM) and casting are the commonly used conventional processing methods to produce the SiC particle reinforced AMCs parts and the obtainable mechanical performance can basically meet the requirements for the practical applications [32,36], However, there are some significant drawbacks that severely hinder the further development of the AMCs by the conventional methods, such as the expensive PM/casting molds and the complex prepro cessing and postprocessing treatments [15]. Furthermore, due to the limited wettability between the ceramic reinforcing phase and the aluminum matrix, the limited particle/matrix interfacial bond ing ability that results from the low working temperature during the conventional process may further decrease the mechanical per formance of the final products.…”
Section: Introductionmentioning
confidence: 99%
“…For the last few decades, the aluminum alloys have been widely used in many industrial fields such as aerospace, architectural con struction, and automotive, because of the nature of lightweight, high corrosion resistance, high thermal conductivity, etc [13][14][15], In order to meet the demand of the more comprehensive mechani cal properties (e.g., the enhanced tensile strength and wear/ tribological performance), the development of the particle rein forced aluminum matrix composites (AMCs), especially the SiC particle reinforced AMCs, attracts the considerable attention, exhibiting the inspiring prospects for development [30], The SiC particle reinforced AMCs have the significant potential for the applications in the aircraft and automotive industries, because of the characteristics of lightweight, high strength, high elastic mod ulus, good wear resistance, and low coefficient of thermal expan sion [31][32][33], Currently, the parts manufactured from the SiC particle reinforced AMCs have been successfully applied in both military and civilian fields, such as aircraft ventral fin [34], wing panels [31], pistons and engine blocks [35], Powder metallurgy (PM) and casting are the commonly used conventional processing methods to produce the SiC particle reinforced AMCs parts and the obtainable mechanical performance can basically meet the requirements for the practical applications [32,36], However, there are some significant drawbacks that severely hinder the further development of the AMCs by the conventional methods, such as the expensive PM/casting molds and the complex prepro cessing and postprocessing treatments [15]. Furthermore, due to the limited wettability between the ceramic reinforcing phase and the aluminum matrix, the limited particle/matrix interfacial bond ing ability that results from the low working temperature during the conventional process may further decrease the mechanical per formance of the final products.…”
Section: Introductionmentioning
confidence: 99%
“…Once the liquid spreads to the particle surface, several processes such as rearrangement, solution-precipitation and grain shape accommodation, contribute to the densification [13]. Near full-dense 6xxx series Al alloy compacts have been successfully fabricated via SLPS of prealloyed powder compacts with and without the addition of sintering aids [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…One disadvantage of this method is the heterogeneous distribution of the SiC particles in the matrix [5][6][7][8][9][10][11][12]. The powder metallurgy (PM) method, as one of the advanced preparation methods, is also commonly used to prepare SiC particle reinforced AlMg-based composite materials [13][14][15][16][17]. Asgharzadeh studied the effect of the SiC content on the SiC distribution and microstructure during the sintering process of a SiC/Al-1.0Mg-0.6Si-0.2Cu-0.1Fe (mass%) composite [15].…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [16] studied the influence of SiC particle contents (25~35 vol.%) on a SiC/Al-1.0Mg-0.6Si-0.2Cu (mass%) composite. It showed that the densification, thermal expansion coefficient of the composite and the tensile strength of the composite decreased with the increasing SiC particle content.The microstructure and properties of SiC particle reinforced PM Al-Mg-based composites are affected by the particle size and volume fraction of the SiC particles, the matrix alloy composition and the sintering process employed [7,9,10,12,15]. Subsequent thermomechanical treatment processes also have an effect on the mechanical properties of composite material, such as the solution treatment process [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation